Recent Seismicity of Western Nepal - Tamang, Bal Bahadur; Dahal, Tirtha Raj; Sharma, Rajesh; Dahal, Anusha (Journal of Nepal Geological Society, 2025)
Geographically, the Himalaya range lies between Namche Barwa in eastern syntaxis and Naga Parbat in western syntaxis. Nepal Himalaya occupies nearly one-third of the 2500 km-long Himalaya range. Geographically, the Nepal Himalaya is differentiated into five stratigraphy, based on the four major tectonic structures, i.e. Main Frontal Thrust (MFT), Main Boundary Thrust (MBT), Main Central Thrust (MCT) and South Tibetan Detachment System (STDS) from South to North. Western Nepal seismicity is controlled by the mid-crustal ramp in the hanging wall of the flat-ramp-flat geometry of the Main Himalayan Thrust (MHT), in contrast to the double-ramp geometry in eastern Nepal. This paper reports the seismic activity in western Nepal, the seismic network, and the earthquake catalogue from 2022 to 2024. Seismic data was acquired under the National Earthquake Monitoring and Research Centre (NEMRC). Western Nepal has a seismic gap of approximately 520 years. Recently, the region has experienced four significant earthquakes: the Doti earthquake (2022-11-08, ML 6.6), the Bajura earthquake (2023-01-24, ML 5.9), the Bajhang earthquake (2023-10-03, ML 6.3), and the Jajarkot earthquake (2023-11-03, ML 6.4). Over 4,800 seismic events were recorded during this period, with a magnitude of completeness (Mc) 2.3 and a b-value 0.75 ± 0.02.